Fragilitas Pendidikan Karakter: Studi Analitis tentang Etika dan Disiplin Siswa Sekolah Dasar - Nurul Hikmah; Putri Hidayati; Syofiani; Rieke Alyusfitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Character education is a fundamental element in shaping ethical behavior and discipline among elementary school students. However, in practice, various problems indicate the weak internalization of character values in students’ daily behavior. This article aims to analyze the condition of students’ ethics and discipline in elementary schools and to examine the factors contributing to the fragility of character education in learning practices. This study employs a qualitative approach with an analytical-reflective design. Data were collected through classroom observations, interviews with several elementary school teachers, documentation analysis, and a review of relevant literature. The findings reveal that the decline in students’ ethics and discipline is influenced by several factors, including changes in the social environment, limited parental involvement in character development, and the challenges of uncontrolled digital technology use. Although various character education efforts have been implemented by teachers and schools, these initiatives tend to produce only temporary effects and have not been sustained. This condition reflects the fragility of character education in elementary schools, highlighting the need for stronger and continuous collaboration among schools, families, and the broader social environment.